Effects of soil compaction by rolling on soil structure and development of maize in no-till and disc ploughing systems on a tropical alfisol - Kayombo, B.; Lal, R. (1986)
A field experiment conducted over three consecutive rainy seasons during 1982–1983 investigated the effects of three levels of seedbed traffic, but with no subsequent traffic, on soil physical properties and growth of maize (Zea mays) using the no-tillage and disc ploughing systems of seedbed preparation. The main treatments consisted of disc ploughing to 20 cm depth followed by harrowing, compared with the no-tillage system. Traffic treatments of 0, 2 and 4 passes of a tractor-drawn 2 Mg roller were sub-plots in a split-plot design experiment. All tillage and traffic treatments were controlled so they always occurred in the same place, season after season. The 4-pass treatment significantly increased penetrometer resistance and dry-soil bulk density, and considerably decreased total porosity, saturated hydraulic conductivity and infiltration rate, more so in disced plots than in no-till plots. The 2-pass treatment had a significant but less marked effect on soil physical properties than the 4-pass treatment. Soil compaction thus resulted in reduced percent emergence, plant height, leaf area index and root growth. Eight weeks after seeding, the root densities in the 0–7 cm soil layer were 2.8, 1.6 and 1.3 mg cm−3 for no-till, and 2.1, 1.3 and 0.9 mg cm−3 for disced plots for 0, 2 and 4 passes, respectively. The 4-pass treatment reduced the mean maize grain yield over three consecutive seasons by 48 and 63% in no-till and disc-ploughed systems, respectively, compared to the zero traffic treatment.